The Effect of Limosilactobacillus reuteri on Social Behavior Is Independent of the Adaptive Immune System - Sean W. Dooling; Martina Sgritta; I-Ching Wang; Ana Luiza Rocha Faria Duque; Mauro Costa-Mattioli (mSystems, 2022)
ABSTRACT Gut microbes can modulate almost all aspects of host physiology throughout life. As a result, specific microbial interventions are attracting considerable attention as potential therapeutic strategies for treating a variety of conditions. Nonetheless, little is known about the mechanisms through which many of these microbes work. Recently, we and others have found that the commensal bacterium Limosilactobacillus reuteri (formerly Lactobacillus reuteri) reverses social deficits in several mouse models (genetic, environmental, and idiopathic) for neurodevelopmental disorders in a vagus nerve-, oxytocin-, and biopterin-dependent manner. Given that gut microbes can signal to the brain through the immune system and L. reuteri promotes wound healing via the adaptive immune response, we sought to determine whether the prosocial effect mediated by L. reuteri also depends on adaptive immunity. Here, we found that the effects of L. reuteri on social behavior and related changes in synaptic function are independent of the mature adaptive immune system. Interestingly, these findings indicate that the same microbe (L. reuteri) can affect different host phenotypes through distinct mechanisms. IMPORTANCE Because preclinical animal studies support the idea that gut microbes could represent novel therapeutics for brain disorders, it is essential to fully understand the mechanisms by which gut microbes affect their host’s physiology. Previously, we discovered that treatment with Limosilactobacillus reuteri selectively improves social behavior in different mouse models for autism spectrum disorder through the vagus nerve, oxytocin reward signaling in the brain, and biopterin metabolites (BH4) in the gut. However, given that (i) the immune system remains a key pathway for host-microbe interactions and that (ii) L. reuteri has been shown to facilitate wound healing through the adaptive immune system, we examined here whether the prosocial effects of L. reuteri require immune signaling. Unexpectedly, we found that the mature adaptive immune system (i.e., conventional B and T cells) is not required for L. reuteri to reverse social deficits and related changes in synaptic function. Overall, these findings add new insight into the mechanism through which L. reuteri modulates brain function and behavior. More importantly, they highlight that a given bacterial species can modulate different phenotypes (e.g., wound healing versus social behavior) through separate mechanisms.